Microsensors in the retention treatment of orthodontic patients - literature review - Joanna Jasińska; Patrycja Łazicka; Eliza Jakubowska; Marta Miziniak; Aleksandra Karolak (Kazimierz Wielki University, 2023)
Introduction Removable retainers have been successfully used for many years as an independent or additional form of retention in patients after orthodontic treatment. Unfortunately, it has been proven that most patients do not follow the orthodontist's recommendations and do not use the braces for the number of hours necessary to stabilize the treatment effects. It has therefore become necessary to look for solutions and devices that are able to objectively record the actual time of retainers use. Aim of the study The aim of the study was to assess the usefulness of electronic microsensors in monitoring wear time of removable retainers. Materials and methods A search was conducted using PubMed, Google Scholar, ResearchGate databases. Articles were searched in English using the following key words: "microsensors", "retention", "orthodontic", "TheraMon", "Smart Retainer". Results The results of the literature review show that microsensors embedded in the elements of removable retainers are a valuable tool for monitoring the time of their use. Awareness of the presence of electronic sensors increases patient discipline. In addition, they provide data that, apart from objectively documenting the course of retention treatment, may be used in the future to determine optimal retention protocols. Conclusions The retention stage is an indispensable element of orthodontic treatment. The use of microsensors built into removable retainers can help to improve the stability of treatment results. However, further research and work are needed to improve the performance and reliability of this type of electronic sensors.